Design and synthesis of non-TZD peroxisome proliferator-activated receptor Î³ (PPARÎ³) modulator - Deka, N.; Uravane, M.; Anthony, J.; Bhumra, S.; Nair, A.; B-Rao, C.; Patel, Dharmeshkumar; Sivaramakrishnan, H. (Birkhaeuser Science, 2014)
Thiazolidinediones (TZDs) are an important class of compound used for the treatment of type 2 diabetes, targeting the peroxisome proliferator-activated receptor Î³ (PPARÎ³). Drug-induced hepatotoxicity, edema, and weight gain are the main concerns associated with TZDs. It was unclear whether the side effects observed are target mediated or compound mediated, but most of the TZDs activate PPARÎ³. This obliged developing of a new diverse class of ligands as antihyperglycemic agents including non-TZD PPAR ligands that could be highly effective, safe, and devoid of side effects. Here, we report the design and synthesis of N-(5-chloro-6-((1-phenylpiperidin-4-yl)oxy)pyridin-3-yl) benzenesulfonamide derivatives as non-TZD PPARÎ³ modulators. Â© Springer Science+Business Media 2013.